Sesquiterpene lactones of plants of the genus Achillea L. (International Journal of Biology and Chemistry, 2026)
Plants of the genus Achillea L. are considered promising sources of medicinal substances based on essential oils, sesquiterpene lactones, and flavonoids. In the present work, the results of a search for sesquiterpene γ-lactones in 13 Achillea species growing in Kazakhstan are summarized for the first time. The distribution of sesquiterpene lactones among the sections of the genus Achillea L. and their classification according to structural types are discussed. Based on chemical and biological screening, the presence of sesquiterpene γ-lactones was established in nine Achillea species. Three species –Achillea inundata Kondr., Achillea salicifolia Besser, and Achillea tianschanica Kupr. & Kulemin — were identified as promising sources for the isolation and identification of sesquiterpene lactones. From Achillea nobilis L. and Achillea micrantha Willd. 11 sesquiterpene lactones have been isolated, including 3 new compounds. The physicochemical characteristics of the isolated sesquiterpene lactones were determined, and their structures were elucidated using IR, UV, 1H NMR, and 13C NMR spectroscopy. An analysis was carried out on the influence of extraction methods, fractionation of crude plant extracts, and purification procedures on the yield of sesquiterpene lactones from Achillea species. Data on the biological activities of the isolated sesquiterpene lactones were compiled and summarized, including antitumor, antitrypanosomal, antileishmanial, anthelmintic activities, and cytotoxicity. The biosynthetic pathways of sesquiterpene lactones in Achillea species are discussed, along with the dynamics of their localization in different plant organs during various stages of vegetation. It was established that sesquiterpene lactones from Achillea species may serve as renewable starting materials for chemical modification and the synthesis of new compounds, representing potential sources of novel antitumor and antiparasitic agents.Keywords: Achillea L., sesquiterpene lactones, qualitative reaction, molecular structure, infrared spectroscopy, nuclear magnetic resonance, X-ray crystallographic analysis, biological activity.